Effect of Implementation of Blended Learning Method on Student Learning Outcomes At Block 5a. Professional Ethics and Health Law in Undergraduate Midwifery Program, Faculty of Medicine Andalas University - Ulfa Farrah Lisa; Yulizawati Yulizawati; Miranie Safaringga (Universitas Andalas, 2021)
Midwives are one of the main health workers as the spearhead of health development in an effort to accelerate the reduction of MMR and IMR. For this reason, midwives who are skilled in conducting clinical procedures are needed with analytical, critical and precise skills in the management of care for women. This can be generated through quality midwife education providers, which are determined by the availability of human resources (lecturers), the quality of infrastructure, classroom learning curricula, laboratory and clinical practice and the condition of the practice area.The learning method is one of the supporting methods for the successful achievement of graduate competencies. This study aims to analyze the effect of the implementation of the blended learning method on the learning outcomes of block 5A midwifery students.Professional Ethics and Health Law in Midwifery Undergraduate Study Program, FK Unand. Design pThis research is a quasi experiment with a control group design research design. The research subjects were given treatment, namely the blended learning method. The analysis used to test the hypothesis is to seedifferences in the mean (average) of data for the treatment group (this year) and the control group (last year) fordetermine whether there is an effect of the implementation of the blended learning method on the learning outcomes of block 5A students. This study applies online learning methods in Block 5A. Respondents who were given treatment in this study were BP18 students, and control respondents were BP17 students who had implemented Block 5A learning in the previous year without using online methods. The results of the unpaired t test with the level of significance (α) are <0.05, which results in a probability value (p) of 0.000, which means that there is an effect of the implementation of the blended learning method on the learning outcomes of Block 5A students. In conclusion, blended learning has a positive impact on increasing the value and motivation of student learning in Block 5A